2021
DOI: 10.3389/fimmu.2021.688918
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensation and Mechanotransduction in Natural Killer Cells

Abstract: Natural killer (NK) cells are a main subset of innate lymphocytes that contribute to host immune protection against viruses and tumors by mediating target cell killing and secreting a wide array of cytokines. Their functions are finely regulated by a balance between activating and inhibitory receptors and involve also adhesive interactions. Mechanotransduction is the process in which physical forces sensed by mechanosensors are translated into chemical signaling. Herein, we report findings on the involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Here, we provide the first evidence that human circulating immune cells are mechanosensitive and harness contractility as a means to induce nuclear translocation of transcription factors to elicit cytotoxicity against NSCLCs. This may explain why previous studies showed a positive graded response of immune response genes (including IFNG ) when immune cells (e.g., T-cells) were cultured on substrates of increasing stiffness ( Saitakis et al, 2017 ; Santoni et al, 2021 ). Also, our findings help explain why an increase in osmolarity due to hemorrhages ( Pirkle and Gann, 1976 ) can result in the activation of infiltrating NK cells that exhibit increased cytotoxicity and chemokine production versus peripheral NK cells ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Here, we provide the first evidence that human circulating immune cells are mechanosensitive and harness contractility as a means to induce nuclear translocation of transcription factors to elicit cytotoxicity against NSCLCs. This may explain why previous studies showed a positive graded response of immune response genes (including IFNG ) when immune cells (e.g., T-cells) were cultured on substrates of increasing stiffness ( Saitakis et al, 2017 ; Santoni et al, 2021 ). Also, our findings help explain why an increase in osmolarity due to hemorrhages ( Pirkle and Gann, 1976 ) can result in the activation of infiltrating NK cells that exhibit increased cytotoxicity and chemokine production versus peripheral NK cells ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, both the activating receptors, NKG2D and DNAM-1, are known to induce actin polymerization through Vav1 ( Xiong et al, 2015 ), which will influence the dynamism of the NK cytoskeletal network. Likewise, the recognition of target cells through β1 and β2 integrins will most likely synergize mechano-responsively in NK cells ( Zhang et al, 2020 ; Santoni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, activation signals are given by activation receptors, for example, Ly49 (D, H, L) and KIR isoforms, NKG2D, and natural cytotoxic receptors such as NKp30 and NKp44 in humans and NKp46 in humans and mice ( 7 , 10 ). Additionally, LFA-1, β1, and β2 integrins can also regulate NK cell function ( 42 ), which we will address later. Signaling of activation and inhibition receptors regulate several NK cells functions, for example, degranulation, morphological modifications to increase NK-target cell contacts, cell migration, and cytokine release.…”
Section: Overview Of Nk Cellsmentioning
confidence: 99%